Social Darwinism - Naomi Beck (Max Planck Institute of Economics, 2012)
In the distant future I see open fields for far more important researches. . . . Light will be thrown on the origin of man and his history. This statement, which appears in the concluding chapter to the Origin of Species, was Darwin's only mention of human evolution in the entire book. Aware of the difficulties his biological propositions would encounter, Darwin thought it wise to leave the delicate question of human evolution aside for the time being. He was nonetheless fully conscious that his theory would revolutionize the way we think about ourselves and our cultures. Enter social Darwinism. The term has been used mainly to decry doctrines that justify some form of individual, social, or racial superiority through evolutionary principles. Yet many of the positions typically attached to social Darwinism do not correspond to this stereotypical description. Even among the main proponents of evolutionary theory in the nineteenth century - Darwin, Wallace, Huxley, and Spencer - there were important disagreements concerning the process of evolution in humans and its results. This article offers an examination of their claims, as well as some related and antagonistic viewpoints, in two main areas: on the one hand, the debate over wealth distribution and landownership, and on the other, the question of the relationship between evolution and ethics.
Keywords: 330; Bioökonomik; Definition